2010
DOI: 10.1029/2009pa001823
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Mediterranean thermohaline circulation to gateway depth: A model investigation

Abstract: [1] The Neogene sedimentary record of the Mediterranean Sea holds evidence for changes in water properties and circulation. These paleoceanographic changes have been attributed to changes in the flow through the ocean gateway between the Mediterranean Sea and the Atlantic Ocean. We use an oceanic general circulation model to achieve quantitative, physics-based understanding of the effect of changes in the depth of the gateway such as may result from tectonic activity or variation in sea level. To isolate these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 87 publications
(126 reference statements)
5
18
1
Order By: Relevance
“…Alhammoud et al (2010) found a similar dependence of the deep outflow from the sill depth in coarse resolution ocean GCM.…”
Section: U Mikolajewicz: Modeling Mediterranean Ocean Climate Of Thesupporting
confidence: 52%
See 1 more Smart Citation
“…Alhammoud et al (2010) found a similar dependence of the deep outflow from the sill depth in coarse resolution ocean GCM.…”
Section: U Mikolajewicz: Modeling Mediterranean Ocean Climate Of Thesupporting
confidence: 52%
“…There is some tendency of an intensification of the deep overturning cell in the western Mediterranean. Alhammoud et al (2010) found a similar response in an idealized Mediterranean setup of on ocean GCM in response to a shallowing of the sill depth.…”
Section: U Mikolajewicz: Modeling Mediterranean Ocean Climate Of Thesupporting
confidence: 52%
“…The sensitivity of circulation in the Late Miocene Mediterranean to changes in the palaeogeography has been examined by Meijer et al (2004). More recently, Alhammoud et al (2010) have examined how the sill depth of the Strait of Gibraltar affects the thermohaline circulation in a highly idealized coarse resolution ocean circulation model.…”
Section: R P M Topper and P Th Meijer: Mediterranean Response Tomentioning
confidence: 99%
“…The surface forcing is idealized and constant in time, and resembles the forcing used in Alhammoud et al (2010). The surface water flux is a constant evaporation of 0.5 m yr −1 over the whole model domain, a value close to presentday evaporation -precipitation -river input (Mariotti et al, 2002), but also suitable for the Late Miocene (Gladstone et al, 2007;Schneck et al, 2010).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation